Multisystem Inflammatory Syndrome in Children (MIS-C) with COVID-19: A Single-Center Experience - Kole, Mehmet Tolga; Yükselmiş, Ufuk; Genç, Fatih Alparslan; Çağ, Yakup; Esen, Feyza Hüsrevoğlu; Pişmişoğlu, Kemal; Karaaslan, Ayşe; Çetin, Ceren; Akin, Yasemin (Journal of Pediatric Infectious Diseases, 2022)
Objective Multisystem inflammatory syndrome in children (MIS-C) is a hyperinflammatory syndrome associated with multiorgan damage that occurs following coronavirus disease 2019 (COVID-19). Research on clinical and laboratory findings, and imaging studies, aiming to predict the progression to severe disease state is limited. This study recruited patients with MIS-C who presented with mild or severe symptoms from a single center in Turkey and evaluated factors related to their symptoms.Methods This retrospective study included 25 pediatric patients with mild and severe presentations of MIS-C. We explored the differences in demographic and clinical data on clinical severity to understand their possible diagnostic and prognostic values.Results Patients with MIS-C had cardiovascular symptoms (68%), gastrointestinal symptoms (64%), dermatologic/mucocutaneous findings (64%), lung involvement (36%), and neurological symptoms (16.0%). About 45.1% of patients with MIS-C had manifestations that overlapped with Kawasaki disease. Eleven patients (44%) were admitted to the intensive care unit, and one (4%) patient died. Grouping based on clinical severity did not differ statistically in terms of gender, age, height, weight, body mass index, and duration of hospital stay. Procalcitonin and ferritin levels correlated with disease severity. The receiver operating characteristic curve for D-dimer gave the highest value of area under the curve, among other biomarkers. The cutoff value for D-dimer was determined as more than 6780.Conclusions Although COVID-19 is usually mild in children, some can be severely affected, and clinical severity in MIS-C can differ from mild to severe multisystem involvement. This study shows that procalcitonin, ferritin, and D-dimer levels may give us information about disease severity.
Keywords: COVID-19; MIS-C; pediatrics; SARS-CoV-2